2017
DOI: 10.1126/science.aal1556
|View full text |Cite
|
Sign up to set email alerts
|

A chemical genetic roadmap to improved tomato flavor

Abstract: Modern commercial tomato varieties are substantially less flavorful than heirloom varieties. To understand and ultimately correct this deficiency, we quantified flavor-associated chemicals in 398 modern, heirloom, and wild accessions. A subset of these accessions was evaluated in consumer panels, identifying the chemicals that made the most important contributions to flavor and consumer liking. We found that modern commercial varieties contain significantly lower amounts of many of these important flavor chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
718
1
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 586 publications
(786 citation statements)
references
References 34 publications
10
718
1
8
Order By: Relevance
“…Indeed, the phenylalanine QTL was even maintained following the application of the highly stringent Bonferroni correction. Since the pathway of starch degradation (which yields sugars) and those related to phenylalanine-derived volatiles contribute to fruit nutritional quality and flavor (Zhang et al, 2015;Tieman et al, 2017), it is possible that these pathways are related to the production of enticing fruits that aid in seed dispersal.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the phenylalanine QTL was even maintained following the application of the highly stringent Bonferroni correction. Since the pathway of starch degradation (which yields sugars) and those related to phenylalanine-derived volatiles contribute to fruit nutritional quality and flavor (Zhang et al, 2015;Tieman et al, 2017), it is possible that these pathways are related to the production of enticing fruits that aid in seed dispersal.…”
Section: Discussionmentioning
confidence: 99%
“…Also, both linkage disequilibrium and linkage mapping indicated that the underlying natural variation in leaf Cd accumulation in the global Arabidopsis population was caused by different Heavy Metal ATPase 3 (At-HMA3) alleles (Chao et al, 2012). Recently, an mGWAS analyzed 28 chemicals specifically associated with consumer preference and flavor intensity, using 2,014,488 common SNPs distributed among 398 modern, heirloom, and wild tomato accessions, which yielded a total of 251 associated loci for 20 traits, including malate content (Tieman et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we analyzed an enlarged mapping population of 272 accessions (Lin et al, 2014;Tieman et al, 2017) with GWAS methods to identify reliable and high precision QTLs that contribute to fruit malate content in a diverse tomato population. Furthermore, we integrated the mGWAS approach with analyses of gene expression patterns, genetic variations, and T-DNA (CRISPR/ Cas9)-derived mutants to functionally characterize a malate contentrelated QTL.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, a mapping experiment is in progress using a larger sample of Oregon Promise doubled haploids. That larger and more robust data set can be used, together with the available barley genome sequence (21) and metabolomic data, to identify candidate genes and biochemical pathways for specific flavors, as described for tomato and cannabis (8,37).…”
Section: Discussionmentioning
confidence: 99%